The role of total factor productivity growth in middle income countries. (Metro Manila, Philippines Asian Development Bank, 2017)
The TFP growth model reveals that the catch up effect, human capital, smaller population, weak currency, and research and development (R&D) growth are significant sources explaining TFP growth. Strengthening innovative activities and building innovative capacities matter in overcoming middle income country challenges. Governments in upper middle income countries need reform to motivate innovation by optimizing national R&D system and redesigning education system targeted toward promoting innovation.
Keywords: Education sector development; social rights -- China; Electronic books